Developing a framework for community childcare doctors to support community-based parental health education in preventing unintentional injuries among children aged below 6 years: a grounded theory exploration in eastern China - Jun Lu; Xiaohong Li; Qian Zhao; Jingwei Xia; Qinghua Xia; Jicui Zheng; Yuheng Feng; Kaiyue Chen (BMJ Open)
Objective Unintentional injuries are a major threat to children’s health. Community-based health management services, which include the prevention of unintentional injuries among children aged 0–6 years, are important basic national public health services. However, deficiencies exist at this stage, such as community childcare doctors not being motivated to provide guidance. Previous studies have explored the impact of the underlying reasons; however, few studies have considered the supporting factors from a social perspective. This study explored the elements supporting community childcare doctors in conducting parental health education and sought to generate a framework capable of providing recommendations.Design A qualitative study was conducted to analyse data collected through semistructured interviews and used the grounded theory method.Setting Interviews were conducted at eight health institutions, health management departments, hospital and universities in four regions of eastern China (Shanghai, Zhejiang, Anhui and Liaoning) and recorded on audio. Interviews were conducted face to face or online.Participants Key informant interviews were conducted with 39 adults (15 parents of children, 11 direct providers of child healthcare and 13 health department managers or experts). The information obtained through interviews included the current situation and difficulties faced by community childcare doctors providing parental health education, the attitudes and perceptions of parents regarding receiving health education and the degree of service acceptance. The independent transcription of interview results was performed by two coders.Results A total of 39 interview transcripts from healthcare service providers, managers and demanders were analysed. Many factors affect the provision of parental health education by community childcare doctors, including the macrodimension and microdimension. Supplier, demander, direct support and indirect support were summarised and reported as both facilitators and barriers to active provision of health services, including 18 subdomains under these four main domains.Conclusions A theoretical model of parental health education based on community childcare doctors was constructed to explain the factors influencing the implementation of education by community childcare doctors. These include individual and socialised behaviours requiring cooperation among individuals, families, governments, the general public and all workers in the healthcare sector. For demanders, it is essential to evoke their beliefs, and for suppliers, it is necessary to improve their skills and stimulate their motivation, both of which cannot be separated from macrolevel support. This model can be used to guide intervention designs aimed at enhancing the enthusiasm of community childcare doctors and further enhancing parental literacy, ultimately achieving the goal of improving children’s health.